Implementation of Risk Management in The Medical Records Work Unit Reviewed From National Standards For Hospital Accreditation Through A Systematic Literature Review Approach - Khairunnisa, Khairunnisa; Rahmadiliyani, Nina (Jurnal Health Sains, 2024)
The hospital, there is no denying the possibility of unwanted or unexpected negative impacts in work activities, one of which is in the medical records work unit. The aim of the research is to determine the implementation of risk management in the medical records work unit in terms of the National Hospital Accreditation Standards. The research method used was a Systematic Literature Review with a search strategy using Google Scholar results criteria with the keywords "Risk management of medical records work units OR Risk management of medical records work units based on SNARS". The research results were obtained from an in-depth analysis of 6 journal articles, there was a link between the journal articles reviewed and the implementation of risk management in the medical records work unit in terms of the National Hospital Accreditation Standards where the problems found on average occurred in MIRM 12 Standards related to the determination of diagnosis code standards , procedure/action codes, symbols, abbreviations and their meanings, MIRM Standard 13 relating to the provision of medical records for each patient in hospitals, MIRM Standard 13.2 relating to hospital regulations which identify those who have the right to fill in patient medical records and determine the contents of medical records and format medical records, MIRM Standard 13.3 relates to filling in medical records by Professional Care Providers (PPA) by writing identification after the recording is made and MIRM Standard 13.4 relates to performance improvement efforts and hospitals regularly evaluating or reviewing medical records. The risk levels in the medical records work unit from these articles show that the risk categories are "Acceptable" (the intensity of risk is reduced to a minimum) to "Substantial" (requires technical improvement).